2008
DOI: 10.1007/s12043-008-0151-8
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced phase transition and stability of EuO and EuS with NaCl structure

Abstract: We have predicted the phase transition pressures and corresponding relative volume changes of EuO and EuS having NaCl-type structure under high pressure using three-body interaction potential (TBIP) approach. In addition, the conditions for relative stability in terms of modified Born criterion has been checked. Our calculated results of phase transitions, volume collapses and elastic behaviour of these compounds are found to be close to the experimental results. This shows that the inclusion of three-body int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 8 publications
3
10
0
Order By: Relevance
“…[16] Using the FP-LAPW scheme in the frame of the GGA. [7] , 36 [9] , 47 [4] 8.9 7.7 [9] 6.5 [3] EuS B1 → B2 22 20 [7] , 21 [13] , 27 [15] , 48.6 [16] , 20 [11] 22 [3] 8.7 14.5 [13] , 11.2 [15] , 6.6 [16] , 12 [11] 12.5 [3] EuSe B1 → B2 18 14 [7] , 9.5 [12] , 24 [15] , 8.9 [16] , 15 [11] 15 [3] 8.4 10.5 [15] , 6.1 [16] , 9.5 [11] 12.8 [3] EuTe B1 → B2 13.5 12 [7] , 9.9 [14] , 17.4 [16] , 10.5 [10] 11 [3] 7.9 8.23 [14] , 7.7 [16] , 8.8 [10] 11.6…”
Section: 661mentioning
confidence: 99%
“…[16] Using the FP-LAPW scheme in the frame of the GGA. [7] , 36 [9] , 47 [4] 8.9 7.7 [9] 6.5 [3] EuS B1 → B2 22 20 [7] , 21 [13] , 27 [15] , 48.6 [16] , 20 [11] 22 [3] 8.7 14.5 [13] , 11.2 [15] , 6.6 [16] , 12 [11] 12.5 [3] EuSe B1 → B2 18 14 [7] , 9.5 [12] , 24 [15] , 8.9 [16] , 15 [11] 15 [3] 8.4 10.5 [15] , 6.1 [16] , 9.5 [11] 12.8 [3] EuTe B1 → B2 13.5 12 [7] , 9.9 [14] , 17.4 [16] , 10.5 [10] 11 [3] 7.9 8.23 [14] , 7.7 [16] , 8.8 [10] 11.6…”
Section: 661mentioning
confidence: 99%
“…At pressure less than 1.8 GPa SmS shows considerable volume collapse and change of colour but retains the same cubic structure [14]. Earlier, we had studied the high pressure phase transition phenomenon, elastic and various thermo-physical properties of SmTe and EuO successfully [15]. For SmS, at zero pressure, the Sm ions are in a divalent insulating state, the so-called black phase [16].…”
Section: Introductionmentioning
confidence: 99%
“…The pressure-volume behavior of EuX (X=O, S, Se, or Te) is somewhat different from that of the other members of the REC family. Several high-pressure studies have been performed on these compounds, and it ws observed that they undergo a first-order transition from a sixfoldcoordinated NaCl (B1) structure with space group Fm3m to an eightfold-coordinated CsCl (B2) structure with space group Pm3m [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Compounds where the Eu ion is in a divalent state (Eu 2+ ) are technologically important semiconducting materials, while compounds where the Eu ion belongs to the trivalent state (Eu 3+ ) due to the promotion of the f electron are metallic.…”
Section: Introductionmentioning
confidence: 99%
“…A study of the structural and elastic properties of these compounds had been reported in the literature [8][9][10][11][12][13][14][15][16][17][18]. The Debye temperatures of Eu compounds have been reported by Shapira et al [11], Benbattouche et al [13], and Subhadra et al [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation